Estoques totais de carbono ecossistêmico e sua potencial vulnerabilidade à elevação do nível do mar em manguezais da Baía de Vitória - Pinto, Lethicia Lellis Vieira (2025)
Mangroves are important carbon sinks, capable of sequestering and storing organic matter through its accumulation in both vegetation and soils. In Vitória Bay, these ecosystems face increasing pressures from mean sea level rise and urban expansion, which limits the landward migration of mangroves. This study was based on the hypothesis that mangroves located at lower elevations, due to their greater exposure to potential erosive processes and frequent inundation, would exhibit lower carbon stocks, as such processes could have removed part of the previously accumulated carbon and compromised their retention capacity. This study aimed to quantify total ecosystem carbon stocks in mangrove forests and to compare these stocks with coastal vulnerability indices in the metropolitan region of Vitória, southeastern Brazil. Total carbon stocks were quantified for six mangrove sites, including aboveground vegetation and soils down to 3 m depth. A guided classification of Vitória Bay was conducted to assess vulnerability based on spatial interpolation maps and the Coastal Sensitivity Index (CSI) developed by Machado and Albino (2024), which considers parameters such as overall vulnerability, elevation, geology/geomorphology, sedimentary features, and proximity to the coastline and river mouths.To compare with the CSI, in situ data on flood frequency and duration, water column depth, and elevation of the mangrove fringe (using RTK GPS) were collected at the six sampled sites. Our results showed that total carbon stocks in the six mangrove forests ranged from 717 to 1481 Mg C ha⁻¹, with an average of 1028 Mg C ha⁻¹, with over 90% of the carbon stored in the soils. The CSI indicated the sampled areas had high overall vulnerability, with site A classified as very high vulnerability, particularly due to its geology/geomorphology and sedimentary characteristics. In situ data classified site A as highly vulnerable, as it showed the lowest average elevation (-1.28 m), indicating greater exposure to flooding. Contrary to the initial hypothesis that mangroves in lower areas would have lower carbon storage capacity due to potential erosion, the lower areas of the Bay of Vitória showed the highest carbon stocks. This suggests that, even under greater physical vulnerability to these pressures, these mangroves continue to play a significant role in carbon retention, possibly due to soil accretion driven by aboveground plant material associated with root systems. This study indicates that, in the protected estuarine mangroves of Vitória Bay, carbon stocks are not primarily associated with vulnerability to coastal erosion related to wave action, highlighting the importance of integrating local hydrodynamic characteristics and terrain topography into conservation strategies and adaptive management in the context of climate change